Diradical reaction mechanisms in [3 + 2]-cycloadditions of hetaryl thioketones with alkyl- or trimethylsilyl-substituted diazomethanes - Mlostoń, Grzegorz; Pipiak, Paulina; Heimgartner, Heinz (Beilstein Journal of Organic Chemistry, 2016)
Reactions of dihetaryl and aryl/hetaryl thioketones with 2-diazopropane, diazoethane, and (trimethylsilyl)diazomethane were studied at variable temperature. The experiments showed that reactions with 2-diazopropane carried out at –75 °C occur mainly via the initially formed, relatively stable 1,3,4-thiadiazolines as products of the [3 + 2]-cycloaddition of the diazo dipole onto the C=S bond. The latter decompose only at higher temperature (ca. −40 °C) to generate thiocarbonyl S-isopropanide. In the absence of the starting thioketone, the corresponding thiiranes and/or ethene derivatives, formed from them via spontaneous desulfurization, are the main products. In contrast, reactions with diazoethane occurred predominantly via initially formed diradicals, which in cascade processes gave sterically crowded 4,4,5,5-tetrahetaryl-1,3-dithiolanes as major products. Finally, the reaction of dihetaryl thioketones with (trimethylsilyl)diazomethane occur smoothly at −75 °C leading to the corresponding 4,4,5,5-tetrahetaryl-1,3-dithiolanes as the exclusive [3 + 2]-cycloadducts formed via a cascade of postulated diradicals. The presence of S or Se atoms in the hetaryl rings is of importance for stabilizing diradical intermediates. Remarkably, in no single case, the ‘head-to-head dimerization’ of aryl/hetaryl and dihetaryl substituted thiocarbonyl ylides was observed.
Keywords: [3 + 2]-cycloadditions; diazoalkanes; diradicals; 1,3-dithiolanes; reaction mechanisms; thioketones